Norwood Aneurysm: Report of a Rare Phenomenon. Issue 2 (March 2023) - Aljohani, Othman A.; Hasan, Ahmad; Byrne, Francesca; Lamberti, John; Murthy, Raghav
An 18-year-old male with complex single-ventricle physiology status post-3-stage palliation developed a large Norwood aneurysm (77 × 67 mm). The patient underwent a successful surgical reconstruction. Care providers must be aware of this rare complication and provide appropriate surveillance.